2010
DOI: 10.1177/0739986310373210
|View full text |Cite
|
Sign up to set email alerts
|

Acculturative Stress Among Documented and Undocumented Latino Immigrants in the United States

Abstract: The purpose of the study was to examine differences between documented and undocumented Latino immigrants in the prevalence of three immigration-related challenges (separation from family, traditionality, and language difficulties), which were made more severe after the passage of restrictive immigration legislation in 1996. Specifically, the study sought to determine the combined and unique associations of legal status, the three immigration-related challenges listed above, and fear of deportation to accultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
258
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(272 citation statements)
references
References 25 publications
(59 reference statements)
10
258
1
1
Order By: Relevance
“…Other studies have argued that while acculturative stress might be highly correlated with discrimination, discrimination is a distinct stressor that impacts one's psychological distress separately [23]. We argue that while acculturative stress is inherent in an individual's efforts to culturally adapt in a new country, discrimination is related to one's ethnic background and socioeconomic status [3,20]. Aiming at a clearer understanding of the immigration challenges impacting Latina immigrant women's mental health, and consistent with previous studies [31], we exclude discrimination from our acculturative stress measure.…”
Section: Introductionmentioning
confidence: 92%
“…Other studies have argued that while acculturative stress might be highly correlated with discrimination, discrimination is a distinct stressor that impacts one's psychological distress separately [23]. We argue that while acculturative stress is inherent in an individual's efforts to culturally adapt in a new country, discrimination is related to one's ethnic background and socioeconomic status [3,20]. Aiming at a clearer understanding of the immigration challenges impacting Latina immigrant women's mental health, and consistent with previous studies [31], we exclude discrimination from our acculturative stress measure.…”
Section: Introductionmentioning
confidence: 92%
“…This may attest to the need for considering socio cultural factors such as a lack of knowledge and understanding about healthy and unhealthy foods readily available in a new host environment for immigrants. Other than diet, chronic stress -which may be experienced by immigrants as they adapt to their new environments -may also play a role in increased risk of metabolic dysfunction [25][26][27][28][29] . Research has shown that chronic stress may lead to energy dysregulation and disruption of brain networks that control eating behavior [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Latino male immigrants who assumed a culturally inherent role for their families (chief breadwinners) may face more distress within the personal autonomy-oriented culture in the United States (Arbona et al, 2010). As such, culturaltransmutation-based stressors may exert particular pressure on Latino men.…”
Section: Research-article2014mentioning
confidence: 99%